2017
DOI: 10.1016/j.str.2016.12.003
|View full text |Cite
|
Sign up to set email alerts
|

Networks of Dynamic Allostery Regulate Enzyme Function

Abstract: SUMMARY Many protein systems rely on coupled dynamic networks to allosterically regulate function. However, the broad conformational space sampled by non-coherently dynamic systems has precluded detailed analysis of their communication mechanisms. Here, we have developed a methodology that combines the high sensitivity afforded by nuclear magnetic resonance relaxation techniques and single-site multiple mutations, termed RASSMM, to identify two allosterically coupled dynamic networks within the non-coherently … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

8
96
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 67 publications
(104 citation statements)
references
References 48 publications
8
96
0
Order By: Relevance
“…We used an NMR-based assay to check for proline isomerization. In this experiment, called 15 N- 1 H ZZ-exchange spectroscopy, the cis and trans resonances of the residue preceding a proline are monitored; upon the addition of enzyme, additional exchange peaks appear in the spectra due to catalysis and the mixing of magnetization during relaxation [3740]. As seen in Supplementary Figure S5, we do not see any exchange peaks indicating active isomerization under the standard experimental conditions tested.…”
Section: Resultsmentioning
confidence: 97%
See 1 more Smart Citation
“…We used an NMR-based assay to check for proline isomerization. In this experiment, called 15 N- 1 H ZZ-exchange spectroscopy, the cis and trans resonances of the residue preceding a proline are monitored; upon the addition of enzyme, additional exchange peaks appear in the spectra due to catalysis and the mixing of magnetization during relaxation [3740]. As seen in Supplementary Figure S5, we do not see any exchange peaks indicating active isomerization under the standard experimental conditions tested.…”
Section: Resultsmentioning
confidence: 97%
“…This might be expected for prolines contained within a fully unstructured polypeptide structure. For now, we do not currently see isomerization under conditions that have worked for other active cyclophilins and their verified substrates [3740]. Finally, we tested for specificity between PPIH and PRPF4 fragments by immobilizing PPIA and testing for the ability of PRPF4 to interact with PPIA when compared with binding to PPIH.…”
Section: Resultsmentioning
confidence: 99%
“…Motions on these timescales are too rapid to be detected by CPMG or CEST experiments that have been used extensively to study s-ms processes in cyclophilin A. 3,25,31,40,41 Likewise relaxation experiments cannot detect motions on this timescale as they are limited to processes occurring faster than the tumbling time  c of cyclophilin A (ca. 10 ns).…”
Section: Preorganization Can Explain Observed Decreases In Catalytic mentioning
confidence: 99%
“…[18][19][20] Because of its significance as a medical target, the catalytic mechanism of CypA has been the subject of extensive studies. 2,3,[21][22][23][24][25][26][27][28][29][30] Computational studies have shown that the speedup of the rate of cis/trans isomerization rate of the prolyl peptide bond is a result of preferential transition-state stabilization through selective hydrogen bonding interactions in the active site of CypA. 26,30 31 More recently, two further mutants were reported in an effort to rescue the lost enzymatic activity of ST.…”
mentioning
confidence: 99%
“…information on the dynamics at room temperature can be obtained with complementary methods, such as nuclear magnetic resonance (NMR) spectroscopy or molecular dynamics (MD) simulations. 10,[14][15][16][17] Other computational methods for the prediction of side-chain geometries include Monte Carlo simulations 18 and bioinformatics analysis using neural networks. 19 MD simulations have gained a significant importance in the fields of biochemistry and biophysics.…”
mentioning
confidence: 99%